Choledochal compression and fistula due to secondary peritoneal hydatidosis - Pomi, Jorge; Bertullo, Hugo; Liard, Washington; Boschi, Jorge (Cirugía del Uruguay, 1975)
The authors report a case of compression of the common hile duct by a inter-cholecysto-duolenal secondary peritoneal hydatic cyst. Its simultaneous fistulization in the choledochus makes it exceptional. The finding was confirmed during surgery and through postoperative X-Rays. The management does not differ from the one used far peritoneal hydatid disease. Immediate evolution is satisfactory, but the long-term prognosis depends on the multiple peritoneal disease.